Ginsenoside Rc ameliorated atherosclerosis via regulating gut microbiota and fecal metabolites - Bin Xie; Xianpeng Zu; Zhicong Wang; Xike Xu; Guoping Liu; Runhui Liu (Frontiers Media S.A., 2022)
Atherosclerosis (AS) and the accompanied cardiovascular diseases (CVDs) were the leading cause of death worldwide. Recently, the association between CVDs, gut microbiota, and metabolites had aroused increasing attention. In the study, we headed our investigation into the underlying mechanism of ginsenoside Rc (GRc), an active ingredient of ginsenosides used for the treatment of CVDs, in apolipoprotein E-deficient (ApoE−/−) mice with high-fat diet (HFD). Seven-week-old male ApoE−/− mice were randomly divided into four groups: the normal control (NC) group, the HFD group, the GRc group (40 mg/kg/d), and the atorvastatin (Ato) group (10 mg/kg/d). Atherosclerotic injury was evaluated by aortic lesions, serum lipid levels, and inflammatory factors. The composition of gut microbiota and fecal metabolite profile were analyzed using 16S rRNA sequence and untargeted metabolomics, respectively. The results showed that GRc significantly alleviated HFD-induced aortic lesions, reduced serum levels of total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), tumor necrosis factor-α (TNF-α), and interleukin (IL)-6 and IL-1β, and increased high-density lipoprotein cholesterol (HFD-C) level, as well as the alteration of gut microbiota composition, function, and metabolite profile. GRc also reversed HFD change of Bacteroidetes and Firmicutes at the phylum level, Muribaculaceae, Lactobacillus, Ileibacterium, Bifidobacterium, Faecalibaculum, Oscillibacter, Blautia, and Eubacterium_coprostanoligenes_group at the genus level, and 23 key metabolites involved in taurine and hypotaurine metabolism, arginine biosynthesis, ATP-binding cassette (ABC) transporters, primary bile acid biosynthesis, purine metabolism, tricarboxylic acid (TCA) cycle, and glucagon signaling pathways. Additionally, eight differential intestinal floras at the genus level were associated with 23 key differential metabolites involving atherosclerotic injury. In conclusion, our results demonstrated that GRc ameliorated atherosclerotic injury, regulated microbial and metabolomic changes in HFD-induced ApoE−/− mice, and suggested a potential correlation among gut microbiota, metabolites, and atherosclerotic injury regarding the mechanisms of GRc against AS.